Pengaruh Lingkungan Kerja Fisik dan Kompensasi terhadap Kinerja Guru MA Ma’arif Udanawu Blitar - Nurul Anisah; Diana Ambarwati; Lina Saptaria (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study discusses the influence of the physical work environment and the damage to the performance of ma'arif Udanawu Blitar teachers. the method used in this research is descriptive quantitative. The population used in this study were the mothers/fathers of teachers in Ma Ma'arif Udanawu Blitar, totaling 86 teachers. The sample used in this study is the entire population, namely 86 samples. The sampling method used is non-probability sampling technique with saturated sampling technique. Data processing in this study is using the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, T Test, F Test and Coefficient of Determination,. The results of this study are that the physical work environment has a partial effect on performance with a significant 0,000 <0,05. Compensation has a partial effect on performance with a significant 0,005 <0,05. The physical work environment and alarms have a simultaneous effect on performance with a significant 0.000 <0.05.